Effect of the C.–1 388 A>G polymorphism in chicken heat shock transcription factor 3 gene on heat tolerance - Wen-wu ZHANG; Li-na KONG; De-xiang ZHANG; Cong-liang JI; Xi-quan ZHANG; Qing-bin LUO (Journal of Integrative Agriculture, 2015)
Heat stress is one of the main factors that influence poultry production. Heat shock proteins (HSPs) are known to affect heat tolerance. The formation of HSPs is regulated by heat shock transcription factor 3 (HSF3) in chicken. A DNA pool was established for identifying single nucleotide polymorphisms (SNPs) of the chicken HSF3, and 13 SNPs were detected. The bioinformatic analysis showed that 8 SNPs had the capacity to alter the transcription activity of HSF3. The dual luciferase report gene assay showed that there was a significant difference (P<0.01) in the Firefly luciferase/Renilla luciferase ratio (F/R) of C.–1 703 A>G (S1) and C.–1 388 A>G (S4) sites at the 5′-untranslated region (UTR) of chicken HSF3. The electrophoretic mobility shift assay showed that the S4 site was a transcription binding factor. The analysis of the association of the S1 and S4 sites with heat tolerance index revealed that the S4 site was significantly correlated with the CD3+ T cell, corticosterone, and T3 levels in Lingshan chickens and with the heterophil/lymphocyte value in White Recessive Rock. These results showed that the S4 site at the 5′ UTR of chicken HSF3 might have an impact on heat tolerance in summer and could be used as a potential marker for the selection of chicken with heat tolerance in the future.